Experimental verification of heat and mass transfer in cargo simulation - Chong, Laurel Yun Ning (2014)
Oil plays a big role is our daily lives and is essential for our daily energy consumption. Hence, emphasis needs placed on the transportation of the oil to refineries and customers globally. To improve the efficiency of the transportation of oil there is a growing need to look into cargo heating management. The process of heating cargo oil can affect fuel consumption significantly during the shipment. Due to the lack of insight into the current software available for cargo heating management, companies do not know exactly how it works and if the heating process is optimized. As a result, the operation of the heating process is based on the crew member’s experience. This could potentially lead to a wastage of fuel and subsequently cost inefficiency. Therefore, there is growing concern on the effective management of cargo heating system. This project is initiated by AET Shipmanagement (Singapore) Pte Ltd. For this project, the aim is to determine a way to save fuel consumption and effectively manage the cargo heating process by operating at the optimum settings. The cargo heating system consist of three main parts; the boilers, cargo tanks and pipelines. This report focuses on one type of cargo oil tank (COT) installed with heating coils. Analysis of the COT will be done through three-dimensional computational fluid dynamics (CFD) simulations using software such as ANSYS-FLUENT. Continuing from previous analysis, this report deals with validating assumptions made. With verified assumptions, simulations for heating the COT are conducted under several operational conditions. Numerical simulations are conducted to set up a database for the various variable inputs that could affect the cargo heating process, accounting for every possible scenario. With the construction of this database, cargo heating management will be more efficient and effective.